ДОСЛІДЖЕННЯ ПРОЦЕСІВ ТА ВИБІР ПАРАМЕТРІВ ІМПУЛЬСНОГО ПІДВИЩУВАЛЬНОГО ПЕРЕТВОРЮВАЧА З АВТОТРАНСФОРМАТОРНИМ УВІМКНЕННЯМ ДРОСЕЛЯ - Руденко, Ю.В.; Мартинов, В.В. (Інститут електродинаміки Національної академії наук України, 2018)
Using the method of averaging in the state space, a mathematical model of DC pulse boost converter with imperfectly magnetically coupled auto-transformer inductor was obtained. Analytical expressions for calculating the parameters of magnetically coupled inductor of converter are determined, which provide the required values ​​of output voltage and current at the allowable voltage loads on the switching element. As a result of the analysis, a technique has been developed for determining the coefficient of transformation and inductance of the inductor windings, selecting the range of variation in the relative duration of control pulses of switching element. To illustrate the calculation procedure, the parameters of converter for high-voltage application are determined. References 6, figure, tables 2.